THE QUALITY OF ORGANOLEPTIC AND TOTAL GOAT MILK BACTERIA WITH THE ADDITION OF A SOLVENT OF CLOVES - F., Narruli; Lindawati, S.A.; Miwada, I N. S. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This study aims to determine the quality of organoleptic and total bacteria pasteurized goat milk by adding clove solution. This study used a Complete Randomized Design (RAL) with four treatments of four repeaters. The four treatments are: P0: Pasteurized goat milk without the addition of a clove solvent, P1: Pasteurized goat milk by the addition of a 1% clove solvent, P2: 160 Pasteurized goat milk by the addition of a 2% clove solvent, P3 : Pasteurized goat milk by the addition of a 3% clove solvent. The observed variables hedonic preference (color, taste and scent), hedonic quality (color, taste and scent), overall and total bacterial acceptance. The results of the organoleptic test were analyzed using general linear procedure univariate model of spss version 26 with analyze non parametric test legacy dialog independent samples while the total bacterial data before analysis were transformed into Logx. Research results showed that goat milk with the addition of clove larval to P0, P1, P2 and P3 treatments obtained a color preference of 3.16-3.88; taste preferences of 2.80-3.68; scent preferences of 3,20-3,64; overall acceptance 3,00-3,60 and total bacteria 1,3x104 – 4,8x104 CFU/ml. The conclusion of this study is that the addition of clove solvents affect color preferences, taste preferences,overall acceptance and total bacteria but does not affect the scent preferences in goat milk with the best treatment and tends to be preferred in P3 treatments.